Genome-wide identification and expression analysis of the HD2 protein family and its response to drought and salt stress in Gossypium species - Bano, Nasreen; Fakhrah, Shafquat; Lone, Rayees Ahmad; Mohanty, Chandra Sekhar; Bag, Sumit Kumar (Frontiers in Plant Science, 2023)
Histone deacetylase 2 (HD2) proteins play an important role in gene expression regulation. It helps the growth and development of plants and also has a crucial role in biotic and abiotic stress responses. HD2s comprise C2H2-type Zn2+ finger at their C-terminal and HD2 label, deacetylation and phosphorylation sites, and NLS at their N-terminal. In this study, a total of 27 HD2 members have been identified using Hidden Markov Model profiles in two diploid cotton genomes i.e. Gossypium raimondii and Gossypium arboreum, and two tetraploid cotton genomes i.e. Gossypium hirsutum and Gossypium barbadense. The cotton HD2 members were classified into 10 major phylogenetic groups (I-X), where group III was found to be most abundant with 13 cotton HD2 members. The evolutionary study showed that the expansion of HD2 members mainly occurred because of segmental duplication in paralogous gene pairs. Further qRT-PCR validations of nine putative genes from RNA-Seq data suggested that GhHDT3D.2 has significantly higher expression at 12h, 24h, 48h, and 72h compared to 0 h (control) in drought as well as in salt stress condition. Furthermore, gene ontology, pathways, and co-expression network study of positively co-expressed genes of GhHDT3D.2 affirmed their significance in drought and salt stress response.